Counting the cost of COVID-19 - Yamin, Mohammad (Int J Inf Technol, 2020)
Coronavirus disease 2019 (COVID-19) is the name given by the World Health Organization (WHO) to the highly contagious and infectious disease caused by the Novel Corona Virus or SARS-CoV-2, which was first reported on 31 December 2019 in Wuhan city of the capital of China's Hubei province. Due to the rapid increase in the number of infections worldwide, the WHO in March 2020, declared COVID-19 as a pandemic. Historically, first coronavirus had surfaced in 1965 with symptoms of common cold. Since then five different strands of this virus have emerged, most lethal of them was the Severe Acute Respiratory Syndrome (SARS), which infected about eight thousand people, killing ten percent of them. The COVID-19 is not the most deadly pandemic world has ever witnessed as the Spanish influenza pandemic, during 1918–19, killed more than fifty million people. Indeed COVID-19 has turned out to be the most lethal of all coronaviruses as it has infected at least three million people killing more than two hundred thousands of them in the first 4 months of its spread. Many politicians and social scientists have dubbed the depression, being caused by COVID-19, worse than that caused by the Second World War. In this article, we shall analyze economic, social, cultural, educational and political impact of the COVID-19.